PENGARUH MOTIVASI KERJA, BUDAYA ORGANISASI, DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DI KEMENTRIAN AGAMA KABUPATEN BANTUL - Salim, Ahmad Fahmi; Prayekti, Prayekti; Yulianto, Eko (Jurnal Manajemen Terapan dan Keuangan, 2025)
This study aims to test whether Work Motivation, Organizational Culture, and Job Satisfaction have an effect on Organizational Citizenship Behavior. The population of the study was 107 employees at the Ministry of Religion of Bantul Regency with a saturated sample technique. Data collection was carried out using a questionnaire. Data were analyzed using SPSS 27 software with Multiple Linear Regression. The results of the study showed that Work Motivation and Job Satisfaction had an effect on Organizational Citizenship Behavior, but Organizational Culture had no effect on Organizational Citizenship Behavior. The results of the study also showed a simultaneous influence between the variables of Work Motivation, Organizational Culture, and Job Satisfaction on Organizational Citizenship Behavior. This study recommends improving or enhancing organizational culture for employees because it is important in terms of fostering Organizational Citizenship Behavior at the Ministry of Religion of Bantul Regency.